The Deletion of Syntactic Function in Sentence Written By Students of Class III, IV, V, And VI Elementary School - Sumadi Sumadi; Novi Eka Susilowati; Suparno Suparno (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2017)
This study aims to describe the deletion of syntactic function in sentences written by students of class III, IV, V, and VI elementary schools. This research data in the form of sentences in class III, IV, V, and VI elementary students. The data were collected from data sources in the form of essays from a number of third-grade students, IV, V, and VI elementary school target of this study. The results showed three things. First, there are sentences found in all classes, namely (1) the constituent sentence essentially present with the basic sentence patterns (a) S-P, (b) S-P-O, (c) S-P-Pel, and (d) S-P-Ket; and (2) a sentence whose constituents are essentially not present with a sentence type whose S constituent is not present. Second, there are sentences found in certain classes, ie (1) sentences whose constituent P is absent only found in class V, and (2) sentences whose S and P constituents are absent are found only in class IV, V, and VI. Thirdly, even though the sentence that his S-constituent is not present is found in all classes, the sentence pattern in each level is different.